An overview of the important points of talent selection in sports - Muniroglu, S.; Subak, E. (Research & Investigations in Sports Medicine, 2018)
Talent selection is the most important phase to train elite athletes for future. In the talent selection stages, there are many important criteria`s have shown in the literature. The age is an important criterion. Besides, physical fitness, anthropometric data`s have used to the testing athletes for talent selection. On the other hand, the cognitive, perceptual and motor skills are also important factors to determine talented individuals. Researchers have conducted many tests for talent selection also include genetic testing nowadays. This review summarizes the most important criteria`s and the most commonly used tests roughly.